Working across religions, cultures, settings, and development: Protocol for wave 2 data collection with children and parents by the developing belief network - Allison J. Williams-Gant; Kara Weisman; Tamer G. Amin; Maliki E. Ghossainy; Ghadir Soueidan; Jenny Nissel; Praveen Kenderla; Marwa Abdel-Hak; Florencia K. Anggoro; Samantha Bangayan; Emily R. R. Burdett; Emily Chau; et al. (PLoS ONE, 2025)
The Developing Belief Network is a global research collaborative studying religious development in diverse social-cultural settings, with a focus on the intersection of cognitive mechanisms and cultural beliefs and practices in early and middle childhood. The current manuscript describes the study protocol for the network’s second wave of data collection, which aims to further explore the development and diversity of religious cognition and behavior using a multi-time point approach. This protocol is designed to investigate three key research questions—how children represent and reason about religious and supernatural agents, how children represent and reason about religion as an aspect of social identity, and how religious and supernatural beliefs are transmitted within and between generations—via a set of eight tasks for children between the ages of 5 and 13 years and a survey completed by their parents/caregivers. This study is being conducted in 41 distinct cultural-religious settings, spanning 16 countries and 12 written languages. In this manuscript, we provide detailed descriptions of all elements of this study protocol, and give a brief overview of the ways in which this protocol has been adapted for use in diverse religious communities. As one example of how this protocol has been implemented outside of the United States, we present Arabic- and English-language study materials for children being raised in one of the following religious traditions in Lebanon: the Druze faith, Maronite Christianity, Orthodox Christianity, Shia Islam, or Sunni Islam. We end with reflections on the challenges of developing and implementing large-scale, multi-site, multi-time point studies of child development; our approach to navigating these challenges; and our suggestions for how future researchers might learn from our experiences and build on the work presented here.